The Role of IL-6 and IGF-1 in Periodontitis Bone Destruction - Ikrima, Abidah; Gunawan, Erwin; Rohmah, Devi Kartika; Bachtiar, Boy Muchlis; Bachtiar, Endang Winiati (Odonto : Dental Journal, 2025)
Periodontitis is an inflammatory condition affecting the tissues supporting the teeth, destroying the periodontal ligament and alveolar bone. This condition is initiated by periodontal pathogens, which trigger an immune response resulting in tissue damage. Pro-inflammatory cytokines, particularly IL-6, have an important role in this process. IL-6, produced by various cells, including immune and periodontal ligament cells, enhances osteoclastogenesis by enhancing RANKL expression, thereby promoting bone resorption. Conversely, IGF-1, a hormone like insulin, is critical in bone homeostasis and regeneration. IGF-1, synthesised in the liver and locally in tissues, aids in the proliferation and differentiation of osteoblasts and osteoclasts, facilitating bone remodelling. IGF-1 also interacts with IL-6 to modulate inflammatory responses and osteoclast activity. Understanding the interplay between IL-6 and IGF-1 offers insights into the mechanism of bone resorption in periodontitis and identifies potential therapeutic targets. This study aims to elucidate the roles of IL-6 and IGF-1 in periodontitis-induced bone resorption and explore their therapeutic implications for periodontal health.